The role of libraries and librarians in promoting access to and use of open educational resources in Tanzania: the case of selected public university libraries - Mwinyimbegu, Chausiku M (University of Dar es Salaam Library Journal, 2020)
This paper examined the role of libraries and librarians in promoting access to and use of Open Educational Resources (OERs) in selected Tanzanian public university libraries. Specifically, the study sought to find out the level of OERs awareness among librarians and the role played by librarians in promoting access to and use of OERs in Tanzania. The study also set out to identify challenges encountered by librarians in promoting access to and use of OERs. Fifty two librarians of different ranks and academic qualifications from four public university libraries participated in this study. These were selected using simple random sampling technique. Data were collected through self-administered questionnaires and documentary review. Data collected were analysed using SPSS version 18.0. The findings show that librarians are aware of the concept OERs and also play multiple roles in promoting awareness on OERs. Integration of OERs in university websites facilitates their accessibility and use. The study further reveals that limited awareness on existing OERs and lack of policy guidelines on the use of OERs are major challenges facing librarians in promoting access to and use of OERs. The study recommends more OERs awareness creation campaigns and formulation of institutional OERs policies.